Role of Self-Compassion, Interpersonal Communication Skills and Narcissism in Mental Health - Harkiran (My University, 2019)
The following survey was done to see the impact of self-compassion, interpersonal skills, narcissism in mental health. The sample consisted a total of 120 students of Thapar Institute of Engineering; out of which 60 were boys and 60 were girls. The age range was between 18-25 years. There were three hypotheses; a. Self-compassion would be positively correlated with mental health; b. Interpersonal communication skills would be positively correlated with mental health; c. Narcissism would be negatively correlated with mental health. In this study four questionnaires were used –Self-compassion Scale; Interpersonal Communication Inventory; Mental Health Continuum-Short Form; Narcissistic Personality Inventory. Descriptive statistics were used to describe the results further correlation and regression were computed. Results showed that there was a productive association between mental health and self-compassion, interpersonal communication skills. Therefore, it is recommended to improve good interpersonal communication skills and better self-compassion so that it may contributes in getting a great mental health. However, it was seen that narcissism had no relationship with mental health.
Keywords: Self-compassion, Interpersonal communication skills, Narcissism, Mental health.